PENGARUH PEMBERIAN EPINEPRIN DAN HIDROKORTISON TERHADAP JUMLAH DAN DIAMETER GERMINAL CENTER KELENJAR GETAH BENING TIKUS PUTIH JANTAN WISTAR - Arifah, Siti; Purwanti, Okti Sri (Jurnal Berita Ilmu Keperawatan, 2008)
Stress is a non specific respone of body if the deman of body increase cause a stressor. Stress will increase sympathetic activity with releasing apinephrine and cortisol. Releasing apineprhine and cortisol to long time will reducing imunity system. Stress can reducing lymphosit B expression, but are this response include exchange of amount and diameter of center germinal in lymph node. This research is to purpose to find out epinephrine and cortisol administration make reducing of amount and diametre center germinal of lymph node. Sample in this research are 20 rattus norvegiccus Wistar, divided to 4 group, they are control that administrated NaCl, first experiment administrated epinefrin, second experiment administrated hidrokortisone, and third experiment administrated both epinephrine and hidrocortishone. The sampling technique is simple random sampling, and collecting data taken from lymph node histologic preparation and then observed with ray microscope. The research resulting significance score is 0,000 (p